Adverse Effects of Single Neutrophil Extracellular Trap-Derived Components on Bovine Sperm Function - Claudia Moya; Rodrigo Rivera-Concha; Felipe Pezo; Pamela Uribe; Mabel Schulz; Raúl Sánchez; Carlos Hermosilla; Anja Taubert; Ulrich Gärtner; Fabiola Zambrano (Animals, 2022)
Neutrophil extracellular traps (NETs) play a key role in fertilisation by eliminating microorganisms and entrapping spermatozoa in the female reproductive tract (FRT). The deleterious effects of NETs on spermatozoa have been previously described; however, individual exposure to NET-derived components in bull spermatozoa has not been explored. The aim of this study was to evaluate the effects of the main NET-derived proteins, histone 2A (H2A), neutrophil elastase (ELA), myeloperoxidase (MPO), pentraxin 3 (PTX), cathepsin G (Cat-G), and cathelicidin LL37 (LL-37), at concentrations of 1, 10, and 30 μg/mL, on sperm parameters. Sperm were selected and incubated with different NET-derived proteins for 4 h. Membrane and acrosome integrity, lipoperoxidation, and membrane phospholipid disorders were also evaluated. Bovine polymorphonuclear neutrophil (PMN)/sperm co-cultures were evaluated by scanning electron microscopy and immunofluorescence. All NET-derived proteins/enzymes resulted in a reduction in membrane integrity, acrosome integrity, and lipoperoxidation at a concentration of 30 μg/mL. Bovine PMN/sperm co-cultures showed marked NET formation in the second hour. In conclusion, all NET-derived proteins/enzymes exerted cytotoxic effects on bull sperm, and this effect should be considered in future investigations on the uterine microenvironment and the advancement of spermatozoa in the FRT.